1995
DOI: 10.1159/000267861
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelium Cell Culture as a Model for Evaluation of the Toxicity of Tamoxifen and Chloroquine

Abstract: The retinal pigment epithelium (RPE) removes the outer segments of photoreceptor cells by phagocytosis. We studied the effects of tamoxifen and chloroquine on the activity of the lysosomal enzymes N-acetyl-β-glucosaminidase and cathepsin D in RPE in vitro to evaluate the possible eye toxicity caused by these drugs. The results show decreases in the activities of lysosomal enzymes after drug exposure. The enzymes tested seemed to be more sensitive to tamoxifen than to chloroquine. A profound decrease in the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
2
13
0
1
Order By: Relevance
“…56,57 Extended exposure to tamoxifen can also lead to decreased levels of enzyme activity independent of pH, possible because of an altered delivery of lysosomal enzymes. 17,38,58 Our results are also consistent with the small increase in risk for age-related maculopathy in patients treated long term with systemic ␤-blockers. 59 With tamoxifen and timolol, however, the lack of extensive ocular damage in spite of widespread use implies the threat is minimal for most people using moderate doses.…”
Section: Implications For Rpe Healthsupporting
confidence: 87%
See 1 more Smart Citation
“…56,57 Extended exposure to tamoxifen can also lead to decreased levels of enzyme activity independent of pH, possible because of an altered delivery of lysosomal enzymes. 17,38,58 Our results are also consistent with the small increase in risk for age-related maculopathy in patients treated long term with systemic ␤-blockers. 59 With tamoxifen and timolol, however, the lack of extensive ocular damage in spite of widespread use implies the threat is minimal for most people using moderate doses.…”
Section: Implications For Rpe Healthsupporting
confidence: 87%
“…However, rapid screening for compounds able to restore an acidic pH required a fast and reproducible method for elevating lysosomal pH above baseline, and neither fresh murine RPE cells nor A2E added to cultured cells for 3 weeks qualified as high-throughput. Because tamoxifen can elevate lysosomal pH and was previously found to be particularly effective at interfering with lysosomal enzyme activity in RPE cells, 16,38 its effect was characterized. Tamoxifen led to a rapid alkalinization; lysosomal pH reached maximal levels within 10 to 12 minutes and remained elevated for the entire 30 minutes of observation (Fig.…”
Section: Model For Rapid Elevation Of Lysosomal Phmentioning
confidence: 99%
“…This evidence agreed with the previous in vivo histopathology reports showing RPE damage with lysosomal residual bodies, by electron microscopy, in APB-administered rats. 18,19 It is widely known that chloroquine induces intracellular pH alterations 29 and cathepsin D inhibition 10 in the RPE, leading to retinopathy. 26,30 It was suggested that weak base amines, like chloroquine, may preferentially accumulate in acidic compartments such as lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…9 Chloroquine was reported to possess lysosomal pH alteration properties. 10 Lysosomes contain various acid hydrolases, including cathepsins, and degrade old, unneeded intracellular substances. 9 During autophagy, lysosomes fuse into autophagosomes and form autolysosomes that degrade a variety of substances.…”
Section: Introductionmentioning
confidence: 99%
“…It appears to have an affinity for retinal pigment epithelium interfering with its catabolism [30,31] and axonal degeneration with lesions located in the nerve fiber and inner plexiform layers [10]. Tamoxifen-induced retinopathy has been well described both for high dosage [9][10][11] and for low-dosage usage [12,13,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%